(untitled) (Advances in Knowledge Representation, 2022)
Knowledge Management remains a recurring theme in congresses, scientific journals and companies. This is due to the search to promote the management and use of knowledge in organizations. To evaluate the results of this search, several models emerge, which are a way to assess the level of this management maturity in organizations. In this context, this research aims to analyze the level of maturity in Knowledge Management in the Municipal Department of Finance of the Municipality of Contagem, Minas Gerais, Brazil. This is an exploratory-descriptive research, with a quantitative approach and extensive direct type. An e-survey questionnaire was used, applied to the servers of the aforementioned Secretariat, and the responses were analyzed using the criteria of Kaiser-Meyer-Olkin (dimensionality), Cronbach’s Alpha (reliability), Pearson’s r together with p-Value (validity). ), Mean, Standard Deviation and 95% Confidence Interval. As a result, the Municipal Department of Finance of the Municipality of Contagem is located at level three of five, being called incipient (initial, embryonic), as it seeks to manage knowledge of the critical area of ​​​​success. A total of 37 actions were identified, in order to encourage the elevation of maturity to level four. The longitudinal application of maturity analysis in this Secretariat, as well as in other institutions, are suggestions for future research.